If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 18 = 2y + -3 Reorder the terms: 18 + 3y = 2y + -3 Reorder the terms: 18 + 3y = -3 + 2y Solving 18 + 3y = -3 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 18 + 3y + -2y = -3 + 2y + -2y Combine like terms: 3y + -2y = 1y 18 + 1y = -3 + 2y + -2y Combine like terms: 2y + -2y = 0 18 + 1y = -3 + 0 18 + 1y = -3 Add '-18' to each side of the equation. 18 + -18 + 1y = -3 + -18 Combine like terms: 18 + -18 = 0 0 + 1y = -3 + -18 1y = -3 + -18 Combine like terms: -3 + -18 = -21 1y = -21 Divide each side by '1'. y = -21 Simplifying y = -21
| 3r/7=12 | | 3x-6+x+(3x-6)+8=80 | | (2±√8)/2 | | -3=4(x+1)-3(x-6) | | y=5(7x+80) | | (3x-6)+x+(3x-6)+8=80 | | 2(x-4)=3(x+5)-2 | | 8-2x=2x-8 | | (3+w)(5w+9)=0 | | 5a-3-(a+6)= | | 2(2f-1)=15 | | ht=-16t^2+4624 | | -5n-n= | | 3/5(2f-1)=15 | | 8.4/100 | | 4e+8=2 | | .28x+4x=-8.56 | | x^2+20-1360=0 | | .6x+1=19 | | X-13/3 | | 3/4(x-7)^2 | | 20(3r-27)=3(5r+45) | | 3x^2+20x+7=-4x^2+4x+24 | | 6x^2+2x=-7x | | -28.73+(-42.21)=x | | -3.4x+5.1=-22.1 | | (k+4)(k-3)=0 | | 3x*3+x*2=75x+25 | | -28.73+(-42.21)= | | 35/28 | | 3x*3+x*2=75+25 | | 3y+5n+8= |